1990
DOI: 10.1037/0735-7044.104.1.160
|View full text |Cite
|
Sign up to set email alerts
|

Independence of benzodiazepine and opiate action in the suppression of isolation distress in rat pups.

Abstract: To determine whether benzodiazepines (BDZs) quiet isolation distress in 10-day-old rat pups by causing a release of endogenous opioids, a blockade of the effects of chlordiazepoxide (CDP) by the opiate antagonist naltrexone (NLX) was sought. Nonsedating doses of morphine (MOR) (0.125 mg/kg) and CDP (2.0 mg/kg) were equally effective in reducing ultrasonic vocalizations and other indices of isolation distress. Appropriate blocking agents NLX, (0.5 mg/kg) against MOR and Ro 15-1788 (4.0 mg/kg) against CDP return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 26 publications
6
57
2
Order By: Relevance
“…The central nerve including GABA, opiate and serotonin neuron is thought to be important in the regulation of USVs. It was reported that the USVs were decreased by treatment with benzodiazepines [23], opiates [6] and serotonin receptor agonists [14,24]. These chemicals belong to anti-panic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The central nerve including GABA, opiate and serotonin neuron is thought to be important in the regulation of USVs. It was reported that the USVs were decreased by treatment with benzodiazepines [23], opiates [6] and serotonin receptor agonists [14,24]. These chemicals belong to anti-panic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Infant rats typically respond to separation from their dams and littermates with ultrasonic vocalization (USV) (Blumberg, Efimova, & Alberts, 1992a;Carden, Barr, & Hofer, 1991;Carden & Hofer, 1990a, 1990bHofer & Shair, 1978;Insel, Hill, & Mayor, 1986;Noirot, 1972), which results in the mother's search for and retrieval of them (Smotherman, Bell, Starzec, Elias, & Zachman, 1974). However, in a more-threatening varient of this testing condition (i.e., when an unfamiliar adult male rat is introduced), rat pups suppress separation-induced vocalization (Takahashi, 1992), a finding that can be mimicked through injection of pups with corticosterone (Takahashi & Rubin, 1993).…”
mentioning
confidence: 95%
“…It has consequently been proposed that social isolation is a stressor that releases opioids as other stressors do [64], It may also be observed that maternal separation has been found to be without effect on the activity of opioid systems in one study [65] but to reduce P-endorphin and enkephalin con centrations in some regions of the brain under certain conditions in another [66]. Furthermore, several non opioid drugs, like benzodiazepines, serotonin agonists and some ligands at the NMDA receptor reduce maternal separation-induced distress calls [58,67,68], These obser vations show that they are not dependent solely on opioids. Rather it seems as if ultrasonic distress vocaliza tions are sensitive to anxiolytics in general.…”
Section: Social Motivation In Recently Weaned Rats Is Modified By Opimentioning
confidence: 99%
“…These were diminished by the administration of opioids in several species [58][59][60][61][62], Separation from the mother was supposed to reduce opioid release, and its consequences should hence be reduced by morphine, just as was the case. This implicates that morphine administration subtituted for the mother.…”
Section: Social Motivation In Recently Weaned Rats Is Modified By Opimentioning
confidence: 99%